Relative Effectiveness of Selected Extension Teaching Methods and Their Combinations in Teaching Rural Aquaculturists - J.S., Ojha; P.M., Sinha (Fishery Technology, 2025)
The present study revealed that among three individual extension methods (personal contact, group discussion, bulletin), personal contact was most effective in convincing the rural aquaculturists about the utility of an innovation. Bulletin occupied the last position in the order of effectiveness. Among the combinations of two, personal contact and group discussion resulted in maximum conviction regarding the merit of a new idea. The combination of group discussion and bulletin appeared to be least effective. The combination of personal contact, group discussion and bulletin proved significantly more effective than any of the three extension methods either individually or in combinations of two. The effectiveness of extension methods and their combinations was influenced by the level of education of the people. It may be concluded that in making aquaculture innovations popular with rural aquaculturists, better results can be achieved if the innovations are first exposed to the fish farmers with high level of education who can act as key communicators and multiply extension efforts.